Factors and Conditions for the Manifestation of Proactive Behavior in Children Participating in the NTI-Club Movement - Mikhail E. Goshin; Pavel S. Sorokin (Voprosy obrazovaniya / Educational Studies Moscow, 2024)
The article is devoted to the study of the types, features, conditions and factors of proactive behavior (agency) of children engaged in various practices of the NTI-Club Movement of Russia. The empirical basis for qualitative sociological analysis was the materials (transcripts) of 53 interviews conducted with schoolchildren participating in the NTI-Club Movement from 2019 to 2022. It is shown that the majority of respondents manifest different levels and forms of agency, including "autonomous", when the subject becomes the initiator of proactive action and "cooperative", manifested in the form of searching and joining a team of like-minded people, or creating organized teams and groups. The main factors contributing to the formation of proactive behavior are the favorable educational environment, the support of the immediate environment, primarily family and parents, as well as classmates, friends and teammates. An important role is that of a mentor, a professional in his field, which consists in introducing the child to certain resources where he/her can independently search for information, inspire and motivate the child.  It was important to reveal the detached parental position, which leads to two possible variants of the child's development: either unwillingness to do anything, or development and implementation despite the lack of parental support. The main external barriers hindering the implementation of agency are the school, which puts forward formal educational requirements, as well as the strictly controlling, limiting position of parents. Internal barriers are lack of motivation, uncertainty and fear of the future, as well as the need to overcome one's own inertia. The important fixation of the interview was the idea about two basic motives for the development of proactive behavior (agency). One is a focus on personal well-being, and the other is a public good, which as a rule do not contradict each other, can complement each other, be implemented jointly.